Learning Media Development Using Lectora Inspire for Social Science Subjects - Astriani , Susi; Astuti, Indri; Mering, Aloysius (Sinkron : jurnal dan penelitian teknik informatika, 2021)
This study aims to develop learning media for Lectora Inspire. This study used a research and development (R&D) method and was developed using the dick and carey model into 3 stages, namely the pre-development stage, product development and revision and evaluation trials. Based on the results of data analysis after the product has been validated by the validator, the final product has met the appropriate criteria with an average score of 3.78 for media experts, 3.78 for material experts, and 3.69 for learning design experts. very valid criteria. The results of students' responses to individual group trials were 89.3%, for medium group trials of 92.56% and teacher responses to field trials of 96.53%. Thus, the learning media Lectora Inspire developed is valid, practical and effective enough to be used in social studies learning.